Chronic tarsal conjunctivitis. Issue 1 (December 2016) - Cook, Nicholas; Mushtaq, Fizza; Leitner, Christina; Ilchyshyn, Andrew; Smith, George; Cree, Ian
Abstract Background Toxicity is rarely considered in the differential diagnosis of conjunctivitis, but we present here a new form of toxic conjunctivitis with unusual clinical features. Between 2010 and 2013, a new clinical presentation of chronic conjunctivitis unresponsive to normal treatment was noted within a Primary Care Ophthalmology Service. Methods Retrospective review of case records and histopathology results. Results A total of 55 adult patients, all females, presented with epiphora and stickiness. They did not complain of itch and had had symptoms for an average of 9 months. Clinical examination showed bilateral moderate to severe upper and lower tarsal conjunctival papillary reaction, without corneal or eyelid changes and mild bulbar conjunctival hyperaemia in a third of cases. Biopsies were taken in 15 cases to exclude an atypical infection or lymphoma. Histologically, there was a variable superficial stromal lymphocytic infiltrate, involving the epithelium in more severe cases. The majority of the cells were CD3 positive T-lymphocytes and follicle formation was not noted. The clinical history in all cases included prolonged use of eye make- up and other facial cosmetic products. Clinical symptoms of epiphora settled with topical steroid drops, but the clinical signs of chronic tarsal inflammation persisted until withdrawal of the facial wipes thought to contain the inciting agent, though the exact nature of this remains unclear. Conclusion The presentation, appearances, histological features are consistent with a contact allergen-driven chronic conjunctivitis. Steroid treatment provided good relief of symptoms and patients were advised to avoid potential contact allergens. Management remains difficult. Further research into contact allergies of mucous membranes and identification of its allergens is required.